Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jnutbio.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling and higher sensitivity to ischemia–reperfusion injury in female rats submitted to high-fat high-sucrose diet: An in vivo/ex vivo longitudinal follow-up

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
(71 reference statements)
2
2
0
Order By: Relevance
“…We report higher heart weight-to-tibia length ratio only in M-HFS in comparison to F-HFS, which could be an indicator of cardiac hypertrophy. This result is consistent with our previous work on female Wistar rats fed with HFS diet in which we did not observe an increase in heart/tibia ratio [ 32 ]. Cardiac hypertrophy has been explained in the literature by increased collagen levels or proliferation of cardiac fibroblasts [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We report higher heart weight-to-tibia length ratio only in M-HFS in comparison to F-HFS, which could be an indicator of cardiac hypertrophy. This result is consistent with our previous work on female Wistar rats fed with HFS diet in which we did not observe an increase in heart/tibia ratio [ 32 ]. Cardiac hypertrophy has been explained in the literature by increased collagen levels or proliferation of cardiac fibroblasts [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Sex differences have been reported in the development of prediabetes in terms of glucose homeostasis. Here we have shown that HFS diet induces the development of fasting hyperglycemia and glucose intolerance in HFS rats which is concordant with a previous study using the same diet in female rats [ 32 ]. However, we showed that HFS females had more pronounced glucose intolerance than HFS males with similar impaired fasting blood glucose.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The moderate variation in macronutrient composition (only 20% fat and 20% carbohydrate) of the diet effectively reproduced hepatic oxidative stress obtained with high‐fat or high‐carbohydrate diets in rodents 48,49 . Besides, the period of life chosen for diet exposure, days of diet consumption, sex, and animal species are other variables that should be considered to try explaining the results found in our study.…”
Section: Discussionmentioning
confidence: 51%